Factors Related to Stunting Children Aged 0-59 Months - Santy Elfrida Simanjuntak; Firkawin Zuska; Taruli Rohana Sinaga; Basuki Rahmat (Sarana Ilmu Indonesia (salnesia), 2022)
Stunting is a disorder of children's growth and development characterized by height or length below the age standard due to repeated infections and long-term chronic nutrition. This study aimed to determine the factors associated with stunting in Aek Nauli II Village. This type of quantitative research was cross-sectional design. This research was conducted in Aek Nauli II Village, Pollung District, Humbang Hasundutan Regency. The sample of this research were a total sampling with 98 samples of toddlers in Aek Nauli II Village. Data collection used a questionnaire with structured questions, which consisted of the mother's knowledge variables and stunting parameters (under-five age and height (TB), weight (BB)). Analysis of data processing were univariate, bivariate, and multivariate. Bivariate analysis were chi-square test and multivariate analysis with multiple logistic regression. There was a relationship between maternal age (p-value 0.048), education (p-value =0,002), and knowledge (p-value =0,017) with stunting. Education and knowledge of mothers under five are the dominant factors related to stunting in children aged 0-59 months in Aek Nauli II Village. This study concludes that maternal age, education, and knowledge are related to stunting. The government needs to pay special attention to increasing the education level of prospective mothers in the future, providing various information related to toddler health, parenting patterns, and nutritional intake for children.